2017
DOI: 10.1097/md.0000000000007843
|View full text |Cite
|
Sign up to set email alerts
|

Value of radial probe endobronchial ultrasound-guided transbronchial biopsy and computer tomography-guided transthoracic needle aspiration in the diagnosis of peripheral pulmonary lesions

Abstract: Computer tomography-guided transthoracic needle aspiration (CT-TTNA) is a minimally invasive technique for sampling peripheral lung lesions. Radial endobronchial ultrasound-guided transbronchial biopsy (rEBUS-TBB) is an alternative. The present study analyzed and compared rEBUS-TBB and CT-TTNA in the diagnosis of peripheral pulmonary lesions (PPL).Clinical data of 513 patients with PPL who underwent an rEBUS-TBB or CT-TTNA examination were analyzed retrospectively. The positive diagnostic rate, complication ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
0
16
1
2
Order By: Relevance
“…To our knowledge, this is the first study of color Doppler US-guided transthoracic biopsy entirely using CNB with a high diagnosis accuracy. Many studies have shown that color Doppler US-guided transthoracic FNAB is useful and safe in the diagnosis of peripheral pulmonary lesions [2,17]. In this retrospective observational study in patients with peripheral pulmonary, chest wall and mediastinal lesions, we performed color Doppler US-guided transthoracic CNB with a freehand technique using automated biopsy guns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study of color Doppler US-guided transthoracic biopsy entirely using CNB with a high diagnosis accuracy. Many studies have shown that color Doppler US-guided transthoracic FNAB is useful and safe in the diagnosis of peripheral pulmonary lesions [2,17]. In this retrospective observational study in patients with peripheral pulmonary, chest wall and mediastinal lesions, we performed color Doppler US-guided transthoracic CNB with a freehand technique using automated biopsy guns.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, US-guided biopsy has many advantages over CT in cases of lesions in the pulmonary periphery or mediastinum that are potentially approachable with US guidance [17,24]. When radiography is contraindicated, US has clear advantages.…”
Section: Discussionmentioning
confidence: 99%
“…In ideal situations, all lesions in the pulmonary field should be detectable. However, the diagnostic ability of rEBUS-TBLB was lower compared with percutaneous transthoracic biopsy (25). In clinical practice, the positive diagnostic rate of rEBUS-TBLB was significantly lower in bronchiolar segments compared with others.…”
Section: Discussionmentioning
confidence: 80%
“…While the CT‐TTNB approach achieved exhibited diagnostic performance when evaluating PPLs, the EBUS‐TBB approach was associated with lower complication rates. Indeed, lower complication rates were associated with the EBUS‐TBB approach in all included studies 10,13‐20 . CT‐TTNB was commonly associated with complications including pneumothorax and hemorrhage.…”
Section: Discussionmentioning
confidence: 86%